2001
DOI: 10.1046/j.1468-3083.2001.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psoriasis in Spain (Epiderma Project: phase I)

Abstract: In a population of about 40 million inhabitants, 470,000-570,000 psoriatic subjects constitute an important target for health care issues and further epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
3
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(78 citation statements)
references
References 8 publications
2
68
3
5
Order By: Relevance
“…19 Yet other studies found leveling off or even drastically declining rates of psoriasis prevalence for individuals beyond the age of 70 years compared to younger age classes. 17,[21][22][23][24][25] Thus, in contrast to the relatively high prevalence measured herein, a nation-wide telephone survey in Spain applying essentially the same structured questionnaire recorded only 0.33% age-specific prevalence in persons >70 years old. This was only a quarter of the average psoriasis prevalence measured in the whole target population of this latter study or just one seventh of the highest prevalence rate that was found for age 17 Telephone surveys answered by proxies is a reliable and generally valuable source of information about health conditions of older probands.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…19 Yet other studies found leveling off or even drastically declining rates of psoriasis prevalence for individuals beyond the age of 70 years compared to younger age classes. 17,[21][22][23][24][25] Thus, in contrast to the relatively high prevalence measured herein, a nation-wide telephone survey in Spain applying essentially the same structured questionnaire recorded only 0.33% age-specific prevalence in persons >70 years old. This was only a quarter of the average psoriasis prevalence measured in the whole target population of this latter study or just one seventh of the highest prevalence rate that was found for age 17 Telephone surveys answered by proxies is a reliable and generally valuable source of information about health conditions of older probands.…”
Section: Discussionmentioning
confidence: 64%
“…27,28 This could at least partly explain thedespite divergent ground populations -unexpected high discrepancy between the estimations of psoriasis prevalence in the elderly found with the same questionnaire in the present face-to-face interview and the former telephone survey study. 17 Furthermore, this observation underscores the difficulties in measuring skin-related morbidity of older probands by using proxies sources, and calls for research focusing on the evaluation of the quality of proxy informations in the area of geriatric dermatology.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Psoriasisin Avrupa'daki en yüksek prevalans değerini gösteren Norveç çalışması 8 veya kuzey Amerika'daki hastalık sıklığını bildiren önemli çalışmalar 9 anket çalışmalarıdır. İspanya'da, genel psoriasis prevalansını bildiren ilk çalışma, telefonla görüşme yolu ile yapılan bir anket çalışması olup, güney Avrupa'dan bu ülkede psoriasis prevalansı %1,43 olarak saptamıştır 10 . Psoriasis prevalansının Kuzey Avrupa'da dünyanın diğer bölgelerine göre daha yüksek olduğu kabul edilmektedir 11 .…”
Section: Discussionunclassified